2004
DOI: 10.1530/eje.0.1500201
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin is independently associated with glycosylated haemoglobin

Abstract: Background: In humans, adiponectin has been demonstrated to circulate in inverse proportion to the degree of insulin resistance. Objective: To investigate the association between adiponectin and glycosylated haemoglobin (HbA 1c ) in a population-based study. Design and methods: Two hundred and ninety-seven individuals aged 30 -75 years were enrolled in a cross-sectional study. They included patients with type 2 (non-insulin-dependent) diabetes mellitus and stable, good metabolic control (n ¼ 32) and individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…Experimental studies have shown that adiponectin reduces the plasma concentrations of free fatty acids and triglycerides and improves insulin resistance (19). Because adiponectin possesses anti-inflammatory properties and improves glucose tolerance, hypoadiponectinaemia has been suggested to be a contributor to the pathogenesis of type 2 diabetes mellitus and its vascular complications (20,21). The major finding in the present study was that fasting plasma concentrations of adiponectin were decreased in diabetic patients, proportionate to the severity of retinopathy.…”
Section: Discussionsupporting
confidence: 53%
“…Experimental studies have shown that adiponectin reduces the plasma concentrations of free fatty acids and triglycerides and improves insulin resistance (19). Because adiponectin possesses anti-inflammatory properties and improves glucose tolerance, hypoadiponectinaemia has been suggested to be a contributor to the pathogenesis of type 2 diabetes mellitus and its vascular complications (20,21). The major finding in the present study was that fasting plasma concentrations of adiponectin were decreased in diabetic patients, proportionate to the severity of retinopathy.…”
Section: Discussionsupporting
confidence: 53%
“…Previous cross-sectional studies in adults with type 1 diabetes have shown a variable relationship between adiponectin levels and glycaemic control, with a negative [1], a positive [11] or no correlation at all [13]. In these studies, differences between the sexes were either not found or not reported.…”
Section: Discussionmentioning
confidence: 59%
“…In the general population, the adipocytokine adiponectin is negatively associated with visceral adiposity, fasting glucose levels and insulin resistance [1][2][3]. Low levels precede a decrease in insulin sensitivity [4] and are associated with obesity and the development of type 2 diabetes and cardiovascular disease [5].…”
Section: Introductionmentioning
confidence: 99%
“…Adiponectin levels correlate negatively with visceral and subcutaneous fat areas (25). We and others observed that adiponectin values were higher in women than in men (26) and correlated negatively with BMI (26,27), waist-to-hip ratio, and plasma triglycerides (25,27) but positively with HDL cholesterol (25,27) and A1C (27). In contrast to reports of patients with type 2 diabetes (25,28), we could not observe lower adiponectin concentrations in patients with diabetic retinopathy than in patients without diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 70%